1992
DOI: 10.1123/tsp.6.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation Training, State Anxiety, and Sport Performance: A Psychophysiological Case Study

Abstract: A single-subject research design was used to test the effectiveness of a cognitive-behavioral intervention in reducing state anxiety and improving sport performance. The subject was a small-bore rifle shooter who suffered from high levels of competition-related anxiety. Initially, self-report, physiological, and behavioral measures of baseline state anxiety were obtained during competition. A 6-week intervention program was then implemented. This program included training in relaxation, thought stoppage, refoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…Multimodal interventions have enhanced athletes' attentional focus (Kerr & Leith, 1993), self-confidence (Prapavessis, Grove, McNair, & Cable, 1992;Savoy, 1997), motivation (Beauchamp, Halliwell, Fournier, & Koestner, 1996;Holm, Beckwith, Ehde, & Tinius, 1996), energy management (Crocker, Alderman, & Smith, 1988;Hanton & Jones, 1999;Holm et al, 1996;Kerr & Goss, 1996;Kerr & Leith, 1993;Kirschenbaum, Owens, & O'Connor, 1998;Mamassis & Doganis, 2004;Prapavessis et al, 1992;Savoy, 1993Savoy, , 1997Thomas & Fogarty, 1997), anger management (Brunelle, Janelle, & Tennant, 1999), productive thinking (Crocker et al, 1988;Kirschenbaum et al, 1998), and performance (Bakker & Kayser, 1994;Beauchamp et al, 1996;Daw & Burton, 1994;Groslambert, Candau, Grappe, Dugue, & Rouillon, 2003;Hanton & Jones, 1999;Kendall, Hrycaiko, Martin, & Kendall, 1990;Kerr & Leith, 1993;Kirschenbaum et al, 1998;G. Multimodal interventions combine several mental training techniques into an integrated strategy that targets specific psychobehavioral outcomes of interest, such as performance improvement or mental skill enhancement.…”
Section: Effectiveness Of Multimodal Mental Skills Trainingmentioning
confidence: 99%
“…Multimodal interventions have enhanced athletes' attentional focus (Kerr & Leith, 1993), self-confidence (Prapavessis, Grove, McNair, & Cable, 1992;Savoy, 1997), motivation (Beauchamp, Halliwell, Fournier, & Koestner, 1996;Holm, Beckwith, Ehde, & Tinius, 1996), energy management (Crocker, Alderman, & Smith, 1988;Hanton & Jones, 1999;Holm et al, 1996;Kerr & Goss, 1996;Kerr & Leith, 1993;Kirschenbaum, Owens, & O'Connor, 1998;Mamassis & Doganis, 2004;Prapavessis et al, 1992;Savoy, 1993Savoy, , 1997Thomas & Fogarty, 1997), anger management (Brunelle, Janelle, & Tennant, 1999), productive thinking (Crocker et al, 1988;Kirschenbaum et al, 1998), and performance (Bakker & Kayser, 1994;Beauchamp et al, 1996;Daw & Burton, 1994;Groslambert, Candau, Grappe, Dugue, & Rouillon, 2003;Hanton & Jones, 1999;Kendall, Hrycaiko, Martin, & Kendall, 1990;Kerr & Leith, 1993;Kirschenbaum et al, 1998;G. Multimodal interventions combine several mental training techniques into an integrated strategy that targets specific psychobehavioral outcomes of interest, such as performance improvement or mental skill enhancement.…”
Section: Effectiveness Of Multimodal Mental Skills Trainingmentioning
confidence: 99%
“…Nevertheless, greater confidence in case studies can be developed by planning them rigorously, assessing multiple dependent measures repeatedly, and triangulating evidence, replicating the results across cases, and collecting data in a systematic and logical manner (Smith, 1988). Further, confidence in the internal validity of the case study can be increased by monitoring potentially confounding factors that may provide plausible alternative explanations for the intervention effects (e.g., Prapavessis, Grove, McNair, & Cable, 1992).…”
Section: Nonexperimental Approaches To Evaluationmentioning
confidence: 99%
“…With regards to the sport classification of studies, the results showed that 26 studies (40%) were classified as team sports, 32 (50%) were classified as individual sports, and only 3 studies (5%) combined both sport types. Fifty-three interventions (83%) included sports that require gross motor skills movements, with only one study sampling a fine motor skilled sport in isolation (viz., Prapavessis, Grove, McNair, & Cable, 1992). Turning to the competitive standard of participants, 20 studies (31%) recruited collegiate performers, while elite (n = 4, 6%) and semi-professional populations (n = 3%) were largely neglected.…”
Section: Study Characteristicsmentioning
confidence: 99%